How Much Influencer Marketing Is Undisclosed? Evidence from Twitter - Daniel Ershov; He Yanting; Stephan Seiler (Center for Economic Studies and ifo Institute (CESifo), 2023)
We quantify the prevalence of undisclosed influencer posts on Twitter across a large set of brands based on a unique data set of over 100 million posts. We develop a novel method to detect undisclosed influencer posts and find that 96% of influencer posts are not disclosed as such. Despite stronger enforcement of disclosure regulations, the share of undisclosed posts decreases only slightly over time. Compared to disclosed posts, undisclosed posts tend to be associated with younger brands with a large Twitter following and are posted from smaller accounts that generate higher engagement per follower.
Keywords: C55; M31; M37; M38; 330; social media; influencer marketing; advertising disclosure; consumer protection